Mood and Flow: Comparing the Benefits of Narrative Versus Poetry Writing. (July 2016) - Fink, Lauren; Drake, Jennifer E.
We examined the benefits of a single session of narrative and poetry writing to determine the immediate effects of each on mood and flow. Following a sad mood induction, we randomly assigned participants to a narrative versus poetry format and to an express versus a distract condition. We measured affect before and after writing and asked participants to complete a flow and enjoyment questionnaire after writing. The distract condition improved affect (by increasing positive and decreasing negative affect) more than did the express condition, regardless of writing format. The poetry format resulted in greater enjoyment than the narrative format, but flow did not differ by condition. Results show that, parallel to findings with drawing, writing to distract is a more effective means of mood improvement than writing to express, at least in the short term. Distraction appears to be the driving force leading to greater mood improvement, regardless of writing format.